The Identification of Critical Road Infrastructures - The Case of Baden-Wuerttemberg - Schulz, Carola (KIT Scientific Publishing, 2012)
Today's globalised society highly depends on reliable infrastructure systems like transportation and telecommunication. This doctoral dissertation presents a methodology to identify critical road infrastructures. Critical road sections are those whose failure would entail large costs to society. The dissertation also accounts for aspects like multiple road disruptions and probabilities of failure. Baden-Wuerttemberg in Germany serves as a case study area.